Variability in the Reporting Terminology of Adverse Events and Complications in Ankle Fracture Fixation: A Systematic Review. (February 2020) - St George, Stefan A.; Sadr, Hooman; Angthong, Chayanin; Penner, Murray; Salat, Peter; Wing, Kevin; Younger, Alistair S. E.; Veljkovic, Andrea
Background: Classification systems for the reporting of surgical complications have been developed and adapted for many surgical subspecialties. The purpose of this systematic review was to examine the variability and frequency of reporting terms used to describe adverse events and complications in ankle fracture fixation. We hypothesized that the terminology used would be highly variable and inconsistent, corroborating previous results that have suggested a need for standardized reporting terminology in orthopedics. Methods: Ankle fracture outcome studies meeting predetermined inclusion and exclusion criteria were selected for analysis by 2 independent observers. Terms used to define adverse events and complications were identified and recorded. Discrepancies were resolved by consensus with the aid of a third observer. All terms were then compiled and assessed for variability and frequency of use throughout the studies involved. Reporting terminology was subsequently grouped into 10 categories. Results: In the 48 studies analyzed, 301 distinct terms were utilized to describe complications or adverse events. Of these terms, 74.4% (224/301) were found in a single study each. Only 1 term, "infection, " was present in 50% of studies, and only 19 of 301 terms (6.3%) were used in at least 10% of papers. The category that was most frequently reported was "infection, " with 89.6% of studies reporting on this type of adverse event using 25 distinct terms. Other categories were "wound healing complications" (72.9% of papers, 38 terms), "bone/joint complications" (66.7% of papers, 35 terms), "hardware/implant complications" (56.3% of papers, 47 terms), "revision" (56.3% of papers, 35 terms), "cartilage/soft tissue injuries" (45.8% of papers, 31 terms), "reduction/alignment issues" (45.8% of papers, 29 terms), "medical complications" (43.8% of papers, 32 terms), "pain" (29.2% of papers, 16 terms), and "other complications" (20.8% of papers, 13 terms). There was a 78.6% interobserver agreement in the identification of terms across the 48 studies included. Conclusion: The reporting terminology utilized to describe complications and adverse events in ankle fracture fixation was found to be highly variable and inconsistent. This variability prevents accurate reporting of complications and adverse events and makes the analysis of potential outcomes difficult. The development of standardized reporting terminology in orthopedics would be instrumental in addressing these challenges and allow for more accurate and consistent outcome reporting. Level of Evidence: Level III; systematic review of Level III studies and above.